دراسة متعدد السكريد المحفظي المستخلص من بكتريا Klebsiella planticola على بعض وظائف الخلايا PMNs - اسامة باسم عبد الخالق الصفار (Journal of Madenat Alelem University College, 2011)
Four isolates of K. planticola were obtained from research center; Al-Nahrrin University and University of Baghdad, they were re-identification according to the cultural, biochemical properties. One isolate (Kp4) was selected to be used in the following experiments due to its efficient production of Galacturonic acid (29) µg/ml, typical biochemical characteristics and its consistent properties along the period of study. Extraction and purification of capsular polysaccharides (CPS), Brain Heart Infusion broth with was used to produce CPS. The CPS was extracted by Cetavlon and was purified by alcohols, the purified CPS concentration was estimated reached to (167) µg/ml. Effect of the purified CPS concentrations (5,10,20,50)µg/ml which was isolated from K. planticola (Kp4) on the immune response (in vitro) were investigated. The following (in vitro) immunological tests were performed; viability of polymorphonuclear cells (PMNs), phagocytosis of Candida albicans , migration of (PMNs) under Agaros, the results showed that: -The concentrations of CPS (20, 50) µg/ml decreased the viability percentage of (PMNs), Phagocytic Index (PI) with significant differences (p<0.05) in comparison to the control treatment. The concentration (50) µg/ml inhibited the migration of (PMNs) -The concentrations of CPS (5, 10) µg/ml increased (Phagocytic indexI), with significant differences (p<0.05) in comparison to the control treatment.